2010
DOI: 10.1029/2010jd014187
|View full text |Cite
|
Sign up to set email alerts
|

How vegetation impacts affect climate metrics for ozone precursors

Abstract: [1] We examine the effect of ozone damage to vegetation as caused by anthropogenic emissions of ozone precursor species and quantify it in terms of its impact on terrestrial carbon stores. A simple climate model is then used to assess the expected changes in global surface temperature from the resulting perturbations to atmospheric concentrations of carbon dioxide, methane, and ozone. The concept of global temperature change potential (GTP) metric, which relates the global average surface temperature change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 37 publications
5
84
0
Order By: Relevance
“…Moreover, there is an increasing recognition that different species have different impacts on the Earth system. For instance, CO 2 has a radiative effect, a fertilisation effect on plants and an acidification effect on the ocean, while CH 4 has an indirect effect on ozone, which may further affect the carbon cycle (Collins et al, 2010). These different effects may result in different impacts on ecosystem services, and this needs to be factored in climate metrics (Huntingford et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is an increasing recognition that different species have different impacts on the Earth system. For instance, CO 2 has a radiative effect, a fertilisation effect on plants and an acidification effect on the ocean, while CH 4 has an indirect effect on ozone, which may further affect the carbon cycle (Collins et al, 2010). These different effects may result in different impacts on ecosystem services, and this needs to be factored in climate metrics (Huntingford et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sitch et al, 2007). Collins et al (2010) showed that adding in the effects of surface ozone on vegetation damage and reduced uptake of CO 2 added about 10 % to the methane GTP(20) and could change the sign of the NO x GTPs. Hence the sign of the net impact of NO x emissions is still uncertain.…”
Section: Carbon Cycle Effectsmentioning
confidence: 99%
“…Feed-back processes in the interaction between the atmosphere and the natural ecosystem and/or the natural oceans in a changing climate have been investigated using models updated with new parametrizations developed in EUCAARI (e.g. Collins et al, 2010). …”
Section: Model Development New Parametrizations Feedback Processes mentioning
confidence: 99%